Concept of Predestination in Islam and Christianity: Special Reference to Averroes and Aquinas - Mohamad, Ismail (Jurnal Usuluddin, 1997)
Predestination is a doctrine believed by Muslims and Christians, but there are some problems arise in understanding of it among them. This article tries to view the problems from Islamic and Christian Weltanschauung as presented by the well-known scholars namely Averroes and Aquinas.